Outcomes of Early Endoscopic Realignment of Post-Traumatic Complete Posterior Urethral Rupture (Journal of Dhaka Medical College, 2016)
Objective: To report the experience with patients treated by early endoscopic realignment of complete post-traumatic rupture urethra.Methods: The cross sectional study included 30 patients in Dhaka Medical College Hospital and different private hospitals in Dhaka, Bangladesh, between April 2010 and March 2014 with post traumatic complete posterior urethral disruption. Pre-operative retrograde urethrography (RGU), micturition cysto urethrography (MCU) and ultrasonography (USG) of abdomen were performed to identify and to evaluate the Urethral defect length, the bladder neck competence, the prostate position and extend of pelvic hematoma. In second week after trauma, antegrade and retro-grade urethroscopy were performed to identify both urethral ends and insert a catheter. Before removal of catheter, Patients were followed up by pericatheter urethrogram after 4 weeks completed postoperative period. If extravasation seen, catheter was again maintained for another 2 weeks. Follow up was done by abdominal ultrasound and uroflowmetry 3 monthly up to 6 months and 6 monthly thereafter. RGU and MCU were performed 8 weeks after removal of catheter. Urinary continence and post-operative erectile dysfunction were assessed by direct patient interview.Results: 30 patients in the age group 18-60 years (mean 36 years) were treated. Patients were followed up for 12 to 36 months. Complete healing of the urethra occurred in 10 patients. Passable urethral stricture developed in 12 patients. Complete urethral obstruction occurred in 8 patients.Conclusion: Early endoscopic realignment for complete posterior urethral rupture is a feasible technique with no or minimal intra-operative complications. The technique is successful as the definite line of therapy in reasonable number of patients and it is seems to be effective Intervention for the prevention of inevitable urethral stricture formation.J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 136-140